Acid-assisted hydrothermal synthesis of red fluorescent carbon dots for sensitive detection of Fe(iii). Issue 65 (22nd August 2017) - Tan, Chunlin; Su, Xiuya; Zhou, Chao; Wang, Baoju; Zhan, Qiuqiang; He, Sailing
Abstract : Red-emitting carbon dots (C-dots) were synthesized from p -phenylenediamine ( p -PD) aqueous solution with nitric acid (HNO3 ) assistance by hydrothermal reaction at 200 °C for 2 h. Abstract : Red-emitting carbon dots (C-dots) were synthesized from p -phenylenediamine ( p -PD) aqueous solution with nitric acid (HNO3 ) assistance by hydrothermal reaction at 200 °C for 2 h. p -PD aqueous solution can be transferred to C-dots (or poly( p -PD)) with (or without) the addition of acid. Different acid systems, such as HNO3, H3 PO4 and HF, can directly synthesize red-emitting C-dots, and the fluorescence can be enhanced by increasing the strength of acids. N-CDs, 3.46 nm-average-sized C-dots, prepared in dilute HNO3, have a quantum yield of 15.8% with unique, excitation-wavelength independent emission in the red region (600 and 680 nm) and a broad visible excitation band. Carboxyl, ester and hydroxyl groups on the C-dots surface directly lead to red emission. N-CDs have a certain selective specificity for Fe 3+ detection and the linear range is 10–300 nmol L −1 with a limit of determination of 1.9 nmol L −1 .